1999
DOI: 10.1053/rmed.1999.0573
|View full text |Cite
|
Sign up to set email alerts
|

Delayed chest radiographs and the diagnosis of pneumothorax following CT-guided fine needle aspiration of pulmonary lesions

Abstract: We prospectively studied 64 consecutive patients on whom computerized tomography-guided fine needle aspirations (CT-FNA) of pulmonary lesions were performed to determine whether obtaining a delayed chest radiography (CXR) after CT-FNA is helpful in the diagnosis of post-procedure pneumothorax (PTX). Two of the 64 patients developed a delayed PTX. Only one of the patients with a delayed PTX required chest tube drainage. If patients have no evidence of a PTX immediately after a CT-FNA by CT scan then a delayed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
17
1
1
Order By: Relevance
“…The literature [215,220,224,232,233,246,247] confirms that a vast majority of post-interventional pneumothoraxes could be proven within 4 h by symptoms or imaging procedures. Accordingly, the risk of later-onset pneumothorax is slight.…”
Section: Evidence Gradementioning
confidence: 86%
“…The literature [215,220,224,232,233,246,247] confirms that a vast majority of post-interventional pneumothoraxes could be proven within 4 h by symptoms or imaging procedures. Accordingly, the risk of later-onset pneumothorax is slight.…”
Section: Evidence Gradementioning
confidence: 86%
“…Chest PA taken immediately after TTNB is not suitable for detecting pneumothorax because the development of pneumothorax takes some time to be detected by this method [9,17]. Furthermore, it is not unusual to detect pneumothorax later in patients without overt pneumothorax on initial chest PA taken after 3 hour (delayed pneumothorax) [9,17-19]. Recently, TTNB has come to be performed by means of CT guidance, and it has become a routine clinical procedure to take CT immediately after TTNB to detect pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…They compared the detection rate of pneumothorax by immediate post-TTNB CT and chest PA at 1 and 4 hour in 88 patients. In total, 37 patients (42%) developed pneumothorax; 35 (39.7%) of these were detected by chest CT and 22 (25%) by chest PA. Pneumothorax by chest PA was found in 20 (57.1%) of 35 patients with pneumothorax by CT and in 2 (3.8%) of 53 without pneumothorax by CT. Byrd's group [19] also reported that pneumothorax was detected by immediate post-TTNB CT in 38 of 158 patients (24.0%), and four (3.3%) of 120 patients with a negative result on immediate post-TTNB CT exhibited overt pneumothorax (delayed pneumothorax).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delayed pneumothorax is not well known, varying from 1.4 to 4.5% based on select institution-based studies. [2][3][4] In this study, we determine the population-based estimate of delayed pneumothorax using discharge records in California. Materials: Using the Healthcare Cost and Utilization Project, Agency for Healthcare Research and Quality database, we tracked all patients who have undergone percutaneous needle lung biopsy in ambulatory care settings and were later admitted to a hospital with iatrogenic pneumothorax in California between 2006 and 2010.…”
mentioning
confidence: 99%
“…With the recent FDA issued statement discouraging the use of surgical techniques that rely on morcellation devices due to risk of spreading cancer, there is increasing interest in, and scrutiny of, treatment options like UAE from referring colleagues and the general public (2). In 2014, SIR updated its quality improvement guidelines for UAE, with a focus on patient selection and informed consent (3,4). According to the updated guidelines, with proper selection and informed consent, women who desire future pregnancy may undergo UAE.…”
mentioning
confidence: 99%